Inovasi Pelayanan Publik Pupuk Bersubsidi - Amira, Zalfa; Munajat, Mas Dadang Enjat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the development of Subsidized Fertilizer Public Service Innovation in Tanjungsari Village, Karangpawitan District, Garut Regency. The problems in this research are the complicated bureaucratic flow from external parties, planning that is not based on evaluation so that the same problems continue to occur, low competency of extension workers. The aim of this research is to find out and describe the process of improving innovation in Subsidized Fertilizer public services in Tanjungsari Village, Karangpawitan District, Garut Regency. The research method uses qualitative research methods by taking informants who involve actors in the policy of Regulation of the Minister of Agriculture of the Republic of Indonesia Number 10 of 2022. The results of the research show that the process of developing subsidized fertilizer public service innovation has not been implemented optimally. Some of the obstacles found in developing subsidized fertilizer public service innovations are due to a less than optimal learning culture so that service providers are less than optimal in carrying out collaboration and developing innovations for public services. The conclusion of this research is that although the subsidized fertilizer public service has been running well, the development of subsidized fertilizer public service innovation has not been implemented optimally so there are still obstacles in its implementation. Keywords: Innovation, Public Services, Subsidized Fertilizer